Sowing the seeds of sustainability: a deep dive into farmers’ recycling practices of pesticide packaging waste in China - Zhou, Yuepeng; Rao, Fangping (Frontiers in Sustainable Food Systems, 2025)
Despite growing agricultural modernization, a majority of pesticide packaging waste (PPW) remains inadequately recycled in China, posing threats to agricultural sustainability and food safety. Drawing from the nationally representative CRRS dataset encompassing 10 provinces and 2,131 households, this study addresses critical research gaps in PPW management by integrating novel dimensions of farmers’ cognition, infrastructure accessibility, and regional heterogeneity, using both multinomial logit (MNL) and propensity score matching (PSM) methods. Our findings show that farmers’ awareness of PPW’s harm on soil and the environment positively influences recycling behavior, while cognitive obstacles negatively impact recycling likelihood. Farmer perspectives on food security demonstrate a dual role, indicating a potential knowledge gap regarding the harmful consequences of burying or burning PPW. The results also highlight that the presence of fixed collection points significantly enhances farmers’ recycling practices. The study suggests a need for interventions, such as promoting fixed collection points and targeted educational programs, to enhance awareness and dispel misconceptions. A comprehensive policy approach, integrating infrastructure development, education, and community engagement, is crucial for fostering sustainable PPW management, ensuring an environmentally responsible and agriculturally sustainable future.